2001
DOI: 10.1063/1.1366333
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorption of benzene on metal dimer anions: A study by photoelectron detachment spectroscopy

Abstract: Photoelectron detachment spectra of M2(C6H6)− (M=Pt, Pd, Pb) have been measured in the gas phase using photon energies of a Nd:YAG laser. The vibrationally resolved ground state transition from the anion to the neutral reveals an adiabatic electron affinity of (2.01±0.05) eV and (0.88±0.05) eV for Pt2(C6H6) and Pd2(C6H6), respectively. A ground state vibrational energy of (24.2±1) meV has been resolved for Pt2(C6H6). The corresponding vibrational energy of Pt2(C6H6)− amounts to (19.0±1.0) meV. The ground state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The resulting clusters, Pt n O − , react with CO, yielding Pt n and CO 2 , thus providing an example of a complete catalytic cycle in the gas phase 43. In recent research, photoelectron spectroscopy (PES) of Pt 2 C 6 H 6 anions has been reported by Eberhardt and co‐workers,26 and Ptbenzene anion complexes have been produced using a similar cluster ion source, in which no dehydrogenated products were observed. However, based on the high resolution of the RTOFMS, the platinum cluster anion dehydrogenated benzene products are unambiguously observed in our experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting clusters, Pt n O − , react with CO, yielding Pt n and CO 2 , thus providing an example of a complete catalytic cycle in the gas phase 43. In recent research, photoelectron spectroscopy (PES) of Pt 2 C 6 H 6 anions has been reported by Eberhardt and co‐workers,26 and Ptbenzene anion complexes have been produced using a similar cluster ion source, in which no dehydrogenated products were observed. However, based on the high resolution of the RTOFMS, the platinum cluster anion dehydrogenated benzene products are unambiguously observed in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Ab initio calculations have been carried out recently for small benzene–platinum complexes by Balasubramanian and co‐workers,24, 25 and they suggested neutral Pt m (C 6 H 6 ) n complexes had a staircase structure, while the PtC 6 H 6+ complex had a C 6v structure (platinum atom above the benzene molecule centre). However, the small anionic platinum cluster reaction with benzene has rarely been reported, except by Eberhardt and co‐workers,26 who studied Pt 2 (C 6 H 6 ) − ions by photoelectron detachment spectroscopy. The reactions of negative and positive atomic platinum ions with benzene have been studied in detail by El‐Nakat and co‐workers,27 who did not observe products of the reaction of the Pt − ion with benzene.…”
mentioning
confidence: 99%
“…0.91 eV is calculated where a vibrational frequency n vib 1.16 3 10 13 Hz (48 meV) along the Au-C 300 K were used [12]. In the RRK approach, it is assumed that the activated cluster with n atoms has j E ‫ء‬ ͞h͗n vib ͘ quanta of vibrational excitations, where E ‫ء‬ E hn 1 E i is the total energy of the cluster.…”
mentioning
confidence: 99%
“…However, the experimental and theoretical studies of metal-benzene anion complexes are rarely reported. Eberhardt et al [10] carried out the studies on M 2 Bz À (M = Pt, Pd, and Pb; Bz = benzene) cluster anions by photoelectron spectroscopy (PES). Bowen group [30][31][32] also studied the M m ðBzÞ À n (M = Ti, Co, Fe, Ni) cluster anions by PES.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many experimental [5][6][7][8][9][10][11][12][13][14][15] and theoretical [16][17][18][19][20][21][22][23][24][25][26][27][28][29] investigations on the interaction of metal clusters with benzene in gas phase were extensively reported. Kaya group [5][6][7] systematically studied the properties of 3d transition metal-benzene complexes M m (benzene) n (M = Sc, Ti, V, Cr, Mn, Fe, Co, Ni) in the gas phase, including their structures, photodissociation processes, bonding energies and ionization energies.…”
Section: Introductionmentioning
confidence: 99%